RESEARCH BASED LEARNING (RBL) TO IMPROVE CRITICAL THINKING SKILLS - Mahardini, Tiyara; Khaerunisa, Firdaus; Wijayanti, Indah Wahyu; Salimi, Moh (Universitas Sebelas Maret, 2018)
The era disruption carrying a lot of changes, both from field of social, culture, economic and education. In the field education in the face of the disruption, educators must be able to develop four skills, namely communication, collaboration, critical thinking, and creativity. Teachers and prospective educators need to develop critical thinking skills by using learning strategies. So we need a method which appropriated with developing of critical thinking skills. Aims of study are describe concept of Research Based Learning (RBL), concept of critical thinking skills, and relationship of RBL and critical thinking skills. The results of Research Based Learning (RBL) can improve critical thinking skills because in this learning method uses authentic learning, problem-solving, cooperative learning, contextual (hands on & minds on) and inquiry-discovery approaches.